2002
DOI: 10.1104/pp.010880
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Kinase Deficiency Is Associated with Developmental Abnormalities and Reduced Transmethylation

Abstract: Adenosine (Ado) kinase (ADK; ATP:Ado 5Ј phosphotransferase, EC 2.7.1.20) catalyzes the salvage synthesis of adenine monophosphate from Ado and ATP. In Arabidopsis, ADK is encoded by two cDNAs that share 89% nucleotide identity and are constitutively, yet differentially, expressed in leaves, stems, roots, and flowers. To investigate the role of ADK in plant metabolism, lines deficient in this enzyme activity have been created by sense and antisense expression of the ADK1 cDNA. The levels of ADK activity in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
148
2
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 46 publications
6
148
2
3
Order By: Relevance
“…This also may be true in plant cells, in which ADK activity has been observed to increase ‫-5.1ف(‬ to 3-fold) in response to methyl demand (Weretilnyk et al, 2001). The fact that transgenic, ADK-deficient Arabidopsis plants have reduced transmethylation activity supports this view (Moffatt et al, 2002). Thus, the increase in ADK activity we observed in infected N. benthamiana plants also might reflect an increased demand for transmethylation activity in response to virus challenge ( Figure 5).…”
supporting
confidence: 64%
See 3 more Smart Citations
“…This also may be true in plant cells, in which ADK activity has been observed to increase ‫-5.1ف(‬ to 3-fold) in response to methyl demand (Weretilnyk et al, 2001). The fact that transgenic, ADK-deficient Arabidopsis plants have reduced transmethylation activity supports this view (Moffatt et al, 2002). Thus, the increase in ADK activity we observed in infected N. benthamiana plants also might reflect an increased demand for transmethylation activity in response to virus challenge ( Figure 5).…”
supporting
confidence: 64%
“…We cannot explain why only one of the transgenic events caused a difference in ADK activity, despite high levels of transgene expression in the case of the sense and antisense lines. But in several respects, our experience has been similar to that of Moffatt et al (2002), who previously constructed transgenic Arabidopsis ADK lines. These investigators found that all lines examined (eight containing sense and four containing antisense ADK constructs) had reduced ADK activity, suggesting varying degrees of silencing, and that reversion to the wild type was frequent (10 to 15% of plants in each generation).…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Purified plastids were extracted with 20% trichloroacetic acid, and SAM recovered in the soluble fraction was converted to fluorescent isoindoles subsequently analyzed by HPLC (Capdevila and Wagner, 1998;Moffatt et al, 2002).…”
Section: Determination Of Plastid Sam Concentrationmentioning
confidence: 99%